Wood and meat as complementary sources of sodium for Kanyawara chimpanzees (Pan troglodytes). Issue 1 (24th February 2020) - Venable, Emily M.; Machanda, Zarin; Hagberg, Lindsey; Lucore, Jordan; Otali, Emily; Rothman, Jessica M.; Uwimbabazi, Moreen; Wrangham, Richard
Abstract: Objectives: Sodium, a vital micronutrient that is often in scarce supply for tropical herbivores, is sometimes found at high concentration in decaying wood. We tested two hypotheses for chimpanzees: first, that wood‐eating facilitates acquisition of sodium; second, that wood‐eating occurs in response to the low availability of sodium from other dietary sources. Materials and Methods: We studied the behavior of more than 50 chimpanzees of all age‐sex classes in the Kanyawara community of Kibale National Park, Uganda. We quantified the sodium content of dietary items, including wood samples from tree species that chimpanzees consumed or did not consume. To assess variation in sodium intake, we used 7 years of data on time spent feeding on plant foods, 18 months of data on rates of food intake by adult females, and 20 years of data on meat‐eating. Results: Major dietary sources of sodium were wood, fruits and meat. Chimpanzees consumed wood primarily from decaying trees of Neoboutonia macrocalyx (Euphorbiaceae), which had substantially higher sodium content than all other dietary items tested. Wood‐eating was negatively correlated with fruit‐eating. Females ate wood more often than males, while males had a greater probability of consuming meat at predation events. Discussion: We propose that females ate wood more often than males because females had reduced access to meat, their preferred source of sodium. This hypothesis suggests that the need for sodium is a motivating reason for chimpanzees to consume both meat and wood.